AUTO-IMAGEM NA ADOLESCÊNCIA - Romeu Gomes; Marcelo Medeiros; Maria das Graças Carvalho Ferriani; Maria Aparecida Tedeschi Cano (Universidade Federal de Goias, 1999)
SOLEMNITY-IMAGE IN THE ADOLESCENCE. The adolescence has been in the last years theme of several of our researches and in these, the sexuality emerges with plenty meaning, associated to the intense physical transformations of this age. The construction of the personal identity in this period includes necessarily the body. Objective: to know and to analyse aspects of the body more valued and important for the adolescent. Methodology: Study qualitative study referenced to MINAYO (1993), that proposes an private and deep understanding about social phenomena, anchored in data collected through personal interactions and analysed from the significance that the involved actors attribute to your acts. The study population was constituted of 40 adolescents between 14 and 16 years, of both sexes, in a Public School in Ribeirão Preto-SP, Brazil. In this work we chose the theatrical techniques, about " The body ours of every day " as a theme, and posters, that were elaborated through collage. We analysed the material collected through the technique of content analysis, thematic modality proposed by BARDIN (1979) and we identified the following "sense nucleus": " perfect body" and "being". In a general way, those nucleuses showed us the adolescents' concern with the subjects of the sexuality represented by the courtship; it plans her and the beauty stereotype transmitted by media. The health and educations area professionals need to know the adolescents' concern with relationship to the body and sexuality, to help them to live the experiences with more explanations for the formation of an acceptable solemnity-image.